FAO fisheries circular N.815, rev.8 - FAO (FAO, 1997)
This publication is a complation of aquaculture production statistics for fish, crustaceans, molluscs and other aquatic animals, residures and plants. The following combination of production statistics are presented: by species and by country; by country and species; and by species and by environment. Values of production expressed in terms of US dollars are provided by country, species and species group, thus providing more detail than previous issues of Fisheries Circular N.815